Pengaruh Motivasi Kerja dan Stres Kerja terhadap Kinerja Perawat di Rumah Sakit Umum Daerah Buton Tengah - Iva Asfiani Bandera; Yusuf Sabilu; Nani Yuniar (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Optimal nurse performance is essential to support the quality of health services in hospitals, in Buton Tegah Regional Hospital, nurse performance is still a concern because a number of problems related to nurse productivity and work quality were found, such as inefficient task implementation, and low active involvement in the service team, this problem is related to various factors that affect performance. This study aims to determine the effect of work motivation and work stress on nurse performance at Buton Tengah Regional General Hospital. The type of research used is observational analytical research using a cross-sectional research design with univariate, bivariate and multivariate tests. The population in this study were all nurses at Buton Tengah Regional General Hospital with a sampling technique using the Total Sampling technique of 64 people. Data analysis used the chi square test and logistic regression. The results showed that there was an effect of work motivation on nurse performance at Buton Tengah Regional General Hospital (0.022 <0.05) and there was a significant effect between work stress on nurse performance at Buton Tengah Regional General Hospital (0.009 <0.05).